Complete convergence and strong law of large numbers for arrays of random variables under sublinear expectations. Issue 23 (1st December 2020) - Lin, Yiwei; Feng, Xinwei
Abstract: In this article, complete convergence theorems are obtained for arrays of widely negative dependent random variables under sublinear expectations. We improve the corresponding results in probability space, and provide a new method to prove them. As an application, we obtain the strong law of large numbers for arrays of random variables under sublinear expectations.